Reform des Tarifvertragsrechts und Änderungen der Verhaltensweisen der Tarifpartner als Voraussetzungen für eine wirksame Bekämpfung der Arbeitslosigkeit - Ulrich Wagner (Fachhochschule Pforzheim, 2000)
Zu den wichtigsten Ursachen der Arbeitslosigkeit in der Bundesrepublik Deutschland gehören die gesetzlichen Regelungen zum Zustandekommen von Tarifverträgen, die Verhaltensweisen der Tarifpartner und das wirtschaftspolitische Umfeld. Positive Ansätze beim Aushandeln beschäftigungsgünstiger Tarifverträge können in der Tariföffnungsklausel des Bundesentgelttarifvertrages der chemischen Industrie und dem Tarifvertragswerk 'Phönix' von Ostmetall und der Christlichen Gewerkschaft Metall gesehen werden. Bei Standortsicherungsverträgen zwischen Unternehmensleitungen und Betriebsräten der Firmen Burda und Viessmann werden die Hürden deutlich, die Gesetzgeber, Rechtsprechung und Gewerkschaftsverhalten vor vernünftigen unternehmensbezogenen Regelungen aufgebaut haben. Voraussetzung für beschäftigungsgünstige, flexible Vereinbarungen auf Unternehmensebene ist die Erweiterung der Tariffähigkeit: Betriebsräte müssen tariffähig werden. Damit muss auch die Tarifüblichkeitssperre fallen. Unumgänglich ist eine Neuinterpretation des Günstigkeitsprinzips: Vom Tarifvertrag abweichende Regelungen sollten per Saldo günstig sein dürfen. Außerdem müssen die Sicherung von Arbeitsplätzen und die Schaffung von Arbeitsplätzen für Outsider als günstig interpretierbar sein. Schließlich ist der Flächentarifvertrag nur zu retten, wenn die Tarifpartner, solange die tatsächliche Arbeitslosigkeit über der als unvermeidlich betrachteten Arbeitslosigkeit liegt, Lohnzuwächse vereinbaren, die den beschäftigungsneutralen Verteilungsspielraum nicht ausschöpfen. – – An effective approach to reducing unemployment would be to change both the legal framework for negotiating pay agreements and the behaviour of the negotiating partners. The main causes of unemployment in Germany are: the legal conditions affecting the negotiation of pay agreements; the behaviour of the negotiating partners and the politico-economic environment. Positive approaches to achieving pay agreements which protect those currently employed can be seen in the opening clauses in the national agreement for the chemical industry, and the agreement-guidelines 'Phönix' between Ostmetal (the eastern german employers confederation) and the christian metal union. Pay agreements, negotiated between the board and union representatives, which place securing employment for the employees in the forefront, are often impeded from reaching a sensible local solution by: precedent cases, the law, and the behaviour of the unions. As can be seen with the companies Burda and Viessmann. A precondition for flexible local agreements, which secure the employment of the current employees, is that Union representatives must be given the autonomy to negotiate local conditions. At present it is not permitted by law (Works Council Constitution Act) to negotiate conditions locally which are included in the national agreements. Local agreements can only be reached when the differences from national agreements are such that each and every issue in the local agreement is advantageous for the employee. This must be changed to allow a compromise or trade-off between the issues involved. In addition, securing or generating employment must be considered an advantage. In conclusion, national agreements can only be saved - especially when the current unemployment rate is greater than that considered as unavoidable - when the negotiating partners agree pay increases smaller than the productivity increase including inflation. Summary: An effective approach to reducing unemployment would be to change both the legal framework for negotiating pay agreements and the behaviour of the negotiating partners.
urn:nbn:de:bsz:951-opus-952
Keywords: 330